2013
DOI: 10.1016/j.diagmicrobio.2013.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Rapid method for Mycobacterium tuberculosis identification using electrospray ionization tandem mass spectrometry analysis of mycolic acids

Abstract: Mycolic acids, which play a crucial role in the architecture of mycobacterial cell walls, were analyzed using electrospray ionization tandem mass spectrometry (ESI-MS/MS). A targeted analysis based on the 10 most abundant and characteristic multiple reaction monitoring (MRM) pairs was used to profile the crude fatty acid mixtures from Mtb and several nontuberculous mycobacterial strains. Comparative analysis yielded unique profiles for mycolic acids, enabling the reliable identification of mycobacterial specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 34 publications
2
41
1
5
Order By: Relevance
“…Advantageously, MS can be performed directly on clinical samples, making it an attractive alternative to genotyping methods for robust and rapid identification to the species level (85). In comparison to DNA-based techniques, the usefulness of phenotypic modalities for typing is considered limited or doubtful.…”
Section: Phenotype-based Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Advantageously, MS can be performed directly on clinical samples, making it an attractive alternative to genotyping methods for robust and rapid identification to the species level (85). In comparison to DNA-based techniques, the usefulness of phenotypic modalities for typing is considered limited or doubtful.…”
Section: Phenotype-based Methodsmentioning
confidence: 99%
“…Regarding phage typing, although sometimes useful (72,73), the limited number of mycobacteriophages identified and poor reproducibility make this method impractical for epidemiological studies (74,75). Phenotype-based typing methods, currently under intense investigation, analyze the composition of the mycobacterial cell wall by thin-layer chromatography (76)(77)(78), high-performance liquid chromatography (79,80), gas chromatography (81,82), and mass spectrometry (MS) (83)(84)(85). One promising methods is matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) MS.…”
Section: Phenotype-based Methodsmentioning
confidence: 99%
“…The dry residue was dissolved in 1 ml of the HPLC mobile phase and transferred to HPLC vials for LC-MS/MS analysis. The isolation of mycolic acids from M. tuberculosis H 37 R v strain (ATCC 27294) was done in accordance with the optimized method described by Szewczyk et al (2013) based on the alkaline hydrolysis of the cell wall lipids and the chloroform extraction of mycolic acids.…”
Section: Mycolic Acid Isolation From Bone Samplesmentioning
confidence: 99%
“…Mass spectrometry analyses were carried out as previously described by Szewczyk et al (2013) with the flow injection analysis (FIA) negative electrospray ionization (ESI) Multiple Reaction Monitoring (MRM) MS/MS detection mode. LC-MS/MS analyses were performed on an Agilent 1200 LC system coupled with an AB Sciex 3200 QTRAP mass detector equipped with Turbo V ESI ion source.…”
Section: Mycolic Acid Isolation From Bone Samplesmentioning
confidence: 99%
“…The higher percentage of converters in the Household TB Contact group might have been a consequence of too short an interval between initial M.tb exposure and IGRA testing. The limited sensitivity of IGRA tests, preventing detection of weak mycobacteria-driven immune responses, justifies the search for new antigens with potent immunostimulatory activity and novel diagnostic methods for rapid identification of M.tb infections, in particular the most dangerous ones such as tuberculous meningitis [26][27][28]. A recent study by Fong et al [29] showed that IGRA conversions in serial testing remained a challenging task for clinicians and that using single cut-off point criteria for IGRA might lead to a significant number of false-positive results and overdiagnosis of LTBI.…”
Section: Discussionmentioning
confidence: 99%